2020
DOI: 10.1177/0020764020939596
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of health care workers in Oman during the COVID-19 pandemic

Abstract: Background: COVID-19 disease is one of the most destructive events that humanity has witnessed in the 21st century. It has impacted all aspects of life and all segments of populations, including already vulnerable health care providers. Aims: This study sought to detect the prevalence of mental health issues in sample of physicians and nurses working in several health facilities in Oman. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
166
2
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(228 citation statements)
references
References 28 publications
27
166
2
14
Order By: Relevance
“… Zhu et al 2020 ), stress (Z. Zhu et al 2020 , Badahdah et al 2020 , Elbay et al 2020 ), anxiety ( Dosil Santamaria et al 2020 , Lijun Kang et al 2020, Kurt et al 2020 , Lai et al 2020 , Badahdah et al 2020 , Corbett et al 2020 , Elbay et al 2020 , Yildirim et al 2020 ) and burnout ( Tolomiczenko et al 2005 ), whereas no consistent associations were found for PTSD.…”
Section: Resultsmentioning
confidence: 99%
“… Zhu et al 2020 ), stress (Z. Zhu et al 2020 , Badahdah et al 2020 , Elbay et al 2020 ), anxiety ( Dosil Santamaria et al 2020 , Lijun Kang et al 2020, Kurt et al 2020 , Lai et al 2020 , Badahdah et al 2020 , Corbett et al 2020 , Elbay et al 2020 , Yildirim et al 2020 ) and burnout ( Tolomiczenko et al 2005 ), whereas no consistent associations were found for PTSD.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Further, study done by Badahdah and colleague revealed that 74.1% of health care workers experienced minimal to mild anxiety (35.5% and 38.7%, respectively) whereas, rest (25.9%) reported moderate to severe anxiety (17.7% and 8.3%, respectively). 30 The variations in findings might be due to use of different measurement scales and cut-off points adopted by the studies. Furthermore, the variations in degree of stress and anxiety score might be due to the fact that our country still is in the early stage of corona outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Although psychological symptoms have been found to be particularly high among those working on the frontline during the pandemic [ 5 , 6 , 7 , 8 ], non-frontline heath care workers have also reported such symptoms [ 9 ]. Moreover, these symptoms have been more severe among females and younger workers [ 4 , 10 , 11 ], as well as for those with prior mental health problems [ 12 , 13 ]. In addition to these cases, social sector workers, who have seldom been acknowledged in the recent COVID-19 literature, have also faced risk of infection in their work [ 14 ].…”
Section: Introductionmentioning
confidence: 99%